WhatsApp and political instability in Brazil: targeted messages and political radicalisation - Rafael Evangelista; Fernanda Bruno (Internet Policy Review, 2019)
In the 2018 presidential election, Brazil elected a fringe congressman, Jair Bolsonaro, despite his radical rhetoric that would suffice to shake the public image of any candidate in the world and the lack of traditional resources of his campaign. One of the hypotheses for this electoral success is that his campaign built a specific communication strategy that used internet platforms to communicate directly with different groups of voters. We describe the Brazilian electoral scenario of 2018, focusing on the use of the messaging app WhatsApp. We discuss how Bolsonaro’s campaign tapped into sentiments and perceptions spread by the legacy media, adding a stronger conservatism. We gather evidence of centralised management of WhatsApp chat groups by political actors that emerge from the work of computer scientists research, newspaper articles and our own ethnographic work. The radicalisation of Brazilian politics could be partially explained as an effect of the use of political micro-targeting in a highly concentrated news media ecosystem, and zero-rating policies that fuels WhatsApp popularity, a platform with affordances that favours the spread of misinformation.